Faktor-Faktor yang Memengaruhi Efektivitas Hematinik pada Pasien Hamil di Puskesmas Kecamatan Matraman - Nadia Farhanah Syafhan; Meiliani Shara Suria L; Azizahwati (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
The government has been giving hematinic that contains 200 mg of ferro sulfas and 0.25 mg of folic acid to pregnant patient since 1970, but anaemia prevalence in pregnant patient at Matraman primary health care has been still relatively high. This research aimed to analyze factors that were influencing hematinic effectiveness that has been used by pregnant patient at Matraman primary health care. The method used for this research was cross-sectional study with purposive sampling technique. Data was obtained from the result of laboratory test for haemoglobin level and interview using valid and reliable questionnaire. Respondents of this research were pregnant patient who used hematinics that were given from government and their haemoglobin level had been measured at least twice during their pregnancy. Total respondent who met the inclusion criteria were 85 patients. Based on the result, there were significant association between tea consumption habits and haemoglobin level (p=0.000) and also significant association between patient adherence on hematinic consumption and haemoglobin level (p=0.004). But there were no significant association between dietary habit and haemoglobin level (p=0,105) and between how to consume hematinic and haemoglobin level (p=0,684). This study showed factors influencing hematinic effectiveness were tea consumption habits and patient adherence on hematinic consumption.